Effects of a Laparoscopic Course on Student Interest in Surgical Residency - Madan, Atul K. (Society of Laparoendoscopic Surgeons, 2005)
BACKGROUND: The number of surgical residency applicants has been declining. Early introduction of the discipline of surgery is thought to stimulate early interest in surgical residency. This study investigated the hypothesis that a laparoscopic skills course introduced in preclinical years would stimulate student interest in entering surgical residency. METHODS: Preclinical medical students participated in a laparoscopic skills training course. All students underwent an animate laboratory at the beginning and at the end of the course. Students were divided into 4 separate groups: virtual reality, box trainer, both trainers, and control group. Before and after the course, students were asked their residency interest. First- and second-year medical students participated in the course. RESULTS: Before the course, 56% of the students desired to go into general surgery or a surgical subspecialty. After the course, 49% of the students expressed interest in entering general surgery or a surgical subspecialty. A decrease occurred in students who desired to go into surgical subspecialty residency from 31% to 15% (P=NS), and an increase occurred in students who desired to go into general surgery residency from 25% to 34% (P=NS). No statistically significant difference was seen in the 4 individual training subgroup analyses. CONCLUSIONS: Participation in a laparoscopic skills course does not affect medical student interest in entering surgical residency. A trend was noted in students choosing general surgery over surgical subspecialty training after this course. Surgical educators need to investigate methods to encourage preclinical medical student interest in surgical residencies.